Influence of Helicobacter pylori infection on ghrelin levels in children - Deng, Zhao-Hui (Baishideng Publishing Group Co., Limited, 2012)
AIM: To compare ghrelin levels in plasma and gastric mucosa before and after Helicobacter pylori (H. pylori) treatment in children with H. pylori-associated functional dyspepsia. METHODS: Children with H. pylori-associated functional dyspepsia were enrolled in this study. H. pylori infection was confirmed by positive bacterial culture results. All of the children received triple H. pylori eradication therapy (a 2 wk course of omeprazole, amoxicillin, and clarithromycin). The children were divided into two groups based on the success of the H. pylori treatment: group 1 (eradicated) - patients who had a negative 13C-urea breath test 2 mo after the end of therapy; and group 2 (non-eradicated) - patients who had a positive 13C-urea breath test. Plasma ghrelin, gastric ghrelin mRNA, and the body mass index were evaluated in both groups before and after the H. pylori treatment. The plasma ghrelin levels were measured by a radioimmunoassay. The expression of gastric ghrelin mRNA was determined by real-time reverse transcription polymerase chain reaction. RESULTS: A total of 50 children with H. pylori-associated functional dyspepsia were treated with triple H. pylori eradication therapy. The mean age of the children was 5.52 ± 0.83 years, and there were 28 males and 22 females. Among the 50 H. pylori-positive children, 30 successfully achieved eradication, and 20 did not. The mean plasma ghrelin levels of group 1 were 22.17 ± 1.73 ng/L and 26.59 ± 2.05 ng/L before and after the treatment, respectively, which was a significant increase (P = 0.001). However, the mean plasma ghrelin level of group 2 before and after the H. pylori treatment was 21.34 ± 2.40 ng/L and 22.24 ± 2.10 ng/L (P = 0.785). The plasma ghrelin levels increased substantially after treatment in group 1 but showed only minor changes in group 2. Similarly, the gastric ghrelin mRNA expression in group 1 before treatment was 2.84 ± 0.08. After treatment, the level was 3.11 ± 0.65, which was significantly different (P = 0.023). The gastric ghrelin mRNA expression in group 2 did not change significantly during the treatment (2.82 ± 0.44 vs 2.79 ± 0.31, P = 0.875). The plasma ghrelin and gastric ghrelin mRNA levels in group 1 increased substantially after the treatment but did not do so in group 2. In addition, the body mass index the two groups did not differ significantly 2 mo before and after the H. pylori treatment. CONCLUSION: H. pylori eradication increases the plasma and tissue ghrelin levels in children with H. pylori-associated functional dyspepsia.